1997
DOI: 10.1095/biolreprod57.5.1193
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Apoptosis in the Temporal and Stage-Specific Loss of Germ Cells in the Adult Rat after Gonadotropin Deprivation1

Abstract: The major objectives of the present study were to document the temporal and stage-specific acceleration of germ cell apoptosis in adult rats after selective suppression of pituitary gonadotropins by GnRH antagonist (GnRH-A) treatment, and to examine the possibility that apoptosis is the sole mechanism of germ cell death in response to hormonal deprivation. Groups of adult male rats were given a daily injection of a vehicle for 14 days or GnRH-A (1.25 mg/kg BW) for 2, 5, 7, and 14 days. Analysis of testicular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
89
0
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 46 publications
6
89
0
6
Order By: Relevance
“…In consequence, this increase possibly causes theca and granulosa cells hypertrophy, changing the follicular morphology and physiology, resulting in probable apoptosis (Wyllie et al, 1980). Sinha-Hikim et al (1997), confirmed the effects of absent hyphophyseal hormones in the ovary of adult rats, which raised the apoptotic cell proportion.…”
Section: Discussionmentioning
confidence: 57%
“…In consequence, this increase possibly causes theca and granulosa cells hypertrophy, changing the follicular morphology and physiology, resulting in probable apoptosis (Wyllie et al, 1980). Sinha-Hikim et al (1997), confirmed the effects of absent hyphophyseal hormones in the ovary of adult rats, which raised the apoptotic cell proportion.…”
Section: Discussionmentioning
confidence: 57%
“…Normally, breaks are physiologically reassembled before spermatozoa are released from germinal epithelium [27], but, as a consequence of testicular injuries, including heat, exposure to toxicant [26,31,34] radiation [37], withdrawal of hormonal support [22,55,61], other testicular pathologies [18] or life habits (smoke, drug use), the repair process could be impaired, so that spermatozoa show high levels of DNA damage [8,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the immature testicle of prepubertal individuals, a massive wave of apoptosis of spermatogonium and primary spermatocytes has been described, due to the absence of adequate levels of gonadotropin (reviewed by [Shaha et al 2010]). During adult life, the apoptotic process responds to hormonal changes [Sinha Hikim et al 1997], to maintain the ratio between Sertoli cells and germ cells (reviewed by [Shaha et al 2010]) and to activate checkpoints monitoring the correct development of spermatogenesis (reviewed by [Morelli and Cohen 2005]). The pachytene checkpoint prevents the progression beyond prophase until DSB repair and homolog synapsis are completed [Li et al 2009].…”
Section: Introductionmentioning
confidence: 99%